Functional echocardiography for management of shock in neonates - study protocol for a randomized controlled trial - Mir, Yaseer A.; Chawla, Deepak; Jain, Suksham; Khurana, Supreet (International Journal of Clinical Trials, 2024)
Background: Shock is common in sick neonates and is associated with a high mortality. Detection and management of shock by monitoring clinical parameters may be inadequate due to inconsistent association with tissue perfusion. We hypothesize that objective assessments of cardiac functions may help to match the pathophysiology of shock with the pharmacological action of a vasoactive drug. This may lead to earlier resolution of shock and reduced incidence of mortality or brain injury. To test this hypothesis, this study aims to evaluate the efficacy of adding functional echocardiography to standard clinical assessment in improving short-term outcome of neonates with clinical features of shock. Methods: This study will be an open-labeled randomized controlled trial, conducted in all inborn neonates born at >27 weeks of gestation who develop clinical signs of shock. Enrolled neonates will be randomized into two groups: the echo group and the control group. Neonates in the echo group will be assessed for management of shock by both standard clinical evaluation and functional echocardiography. Neonates in the control group will be assessed for the management of shock by standard clinical evaluation. Primary outcome will be survival without requirement of inotropic support at 72 hours of randomization. Secondary outcomes include time to hemodynamic stability, duration of inotropic support and incidence of abnormal cranial ultrasound. Conclusions: The trial intends to deduce the advantages, if any, of addition of functional echocardiography to standard clinical assessment to guide management of shock among preterm and term neonates. Trial registration: CTRI number: CTRI/2023/08/056672.